2002
DOI: 10.1074/jbc.m207057200
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Bacterial Capsular Polysaccharides and Lipopolysaccharides by the Macrophage Mannose Receptor

Abstract: The in vitro binding of the macrophage mannose receptor to a range of different bacterial polysaccharides was investigated. The receptor was shown to bind to purified capsular polysaccharides from Streptococcus pneumoniae and to the lipopolysaccharides, but not capsular polysaccharides, from Klebsiella pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 57 publications
1
166
1
3
Order By: Relevance
“…P. aeruginosa slime-GLP, a strong TNF-a inducer, contains mannose, which is absent from the homologous LPS [26,27] and mediates the biological activities of P. aeruginosa slime-GLP [28]. Previous work by Zamze et al [41] demonstrated that P. aeruginosa LPS does not bind MR in vitro, whereas structurally irrelevant LPS from other bacteria do so, suggesting a way of recognition that does not rely on linear epitopes. In agreement with those studies, we herein observe that blocking MR did not exert any effect on TNF-a production through P. aeruginosa LPS, but almost abolished it by slime-GLP and viable P. aeruginosa bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa slime-GLP, a strong TNF-a inducer, contains mannose, which is absent from the homologous LPS [26,27] and mediates the biological activities of P. aeruginosa slime-GLP [28]. Previous work by Zamze et al [41] demonstrated that P. aeruginosa LPS does not bind MR in vitro, whereas structurally irrelevant LPS from other bacteria do so, suggesting a way of recognition that does not rely on linear epitopes. In agreement with those studies, we herein observe that blocking MR did not exert any effect on TNF-a production through P. aeruginosa LPS, but almost abolished it by slime-GLP and viable P. aeruginosa bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…They have been implicated in CNS inflammation and more recently in AD (21). To identify perivascular macrophages, we used CD163, a hemoglobinhaptoglobin scavenger receptor, and CD206, a mannose receptor (20,26,27). Analysis of SR-BI mutant mice revealed a remarkable increase in CD206 and CD163 in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the impact of SR-BI reduction in perivascular macrophages in the mouse brain, we analyzed the expression of CD206 and CD163 in SR-BI +/− and −/− mice. CD206, a mannose receptor, and CD163, a scavenger receptor, have been identified as perivascular macrophage markers (26,27). Analysis of total protein brain extracts by Western blotting showed a significant increase in both CD206 and CD163 in SR-BI +/− and −/− mice compared with wild-type mice (n = 5) (CD206 wild-type versus SR-BI +/− , P = 0.0446; wild-type versus SR-BI −/− , P = 0.0018; CD163 wild-type versus SR-BI +/− , P = 0.0467; wild-type versus SR-BI −/− , P = 0.0064; Fig.…”
Section: Sr-bi Reduction Increases Perivascular Macrophages In the Mousementioning
confidence: 99%
“…Cells were kept in serum-free medium (Opti-MEM; Invitrogen) after transfection, and supernatant was collected after 3 days. Purification of sMR-HA was performed by affinity chromatography using an anti-MR monoclonal antibody (clone MR5D3 purchased from HyCult blotachnology b.v.) conjugated to gammabind plus Sepharose as described (26).…”
Section: Expression and Purification Of A Hemaglutinin-tagged Solublementioning
confidence: 99%